An Analysis of the Impact of Differentiated Instruction on Academic Achievement Among Grade X Students in Vocational Education - Dedi Aviadi; Albert Efendi Pohan; Tubagus Pamungkas (Jurnal Inovasi Pendidikan dan Sains)
This study aims to investigate the effectiveness of implementing differentiated instruction in improving student learning outcomes in Informatics for Grade X students at a vocational high school. Employing a classroom action research design over two cycles, data were collected through learning outcome tests, student attitude observations, and documentation. Both qualitative and quantitative approaches were utilized in data analysis. The findings reveal that the implementation of differentiated instruction was moderately effective, with an average N-Gain score of 75.6%. There was a significant improvement in student learning outcomes following the application of differentiated instructional methods. Quantitative analysis supported the effectiveness of this approach, as evidenced by a t-test value of 6.256 with 66 degrees of freedom and a significance level of < 0.001, thereby rejecting the null hypothesis (H₀). These results indicate that differentiated instruction can significantly enhance student engagement and academic performance, particularly in subjects such as Informatics that require logical and rapid thinking skills. The study underscores the crucial role of instructional innovation and teacher management strategies in addressing diverse student needs and optimizing learning outcomes. It recommends the broader application of differentiated instruction to enhance teaching quality and student achievement in vocational education contexts